Organic matter of virgin and arable soddy-podzolic soil in the Urals - Zavyalova , N.E.; Vasbieva , M.T.; Shishkov , D.G. (Perm Federal Research Centre Journal, 2023)
In a long-term stationary experiment in 1978, the content and qualitative composition of organic matter (Corg) in arable soddy-podzolic soil were studied with the application of various rates NPK, and also compared with virgin soil under mixed forest and grass-forb meadow. It was established that when mineral fertilizers were applied at a dose of 60 kg a.i./ha or more, dynamic balance is ensured in the soil. At the same time, the Corg content stabilized at a level close to the initial level and varied from 1,14 to 1,19%. The share of mobile organic matter in the total carbon of the studied soil was 21–24%, which is typical for soddy-podzolic soils. The distribution of carbon over soil layers is decreasing. The main reserves of organic carbon are concentrated in the 0-40 cm layer and account for 53–65% from stocks in the meter layer (77–101 t/ha). In virgin soil, Corg stockpile in the layer of 0–20 cm are 31–41 t/ha, in the meter layer – 71–82 t/ha. The studied humic acids (HA) in terms of the content of constitutional elements (C, H, N, O, S) correspond to the average values for the class of humic acids in soddy-podzolic soils. With an increase in the rates of mineral fertilizers (NPK), the processes of mineralization of fresh organic matter is more intense, and the proportion of aromatic structures also increases in humic acids composition. According to elemental analysis, the H:C ratio in humic acids of the N150P150K150 variant, was 1,25, and in virgin soil it was 1,43-1,56. According to IR spectroscopy data, vibrations of the C=O group of aromatic rings were revealed in the region of 1 605–1 670 cm-1 at the maximum dose of NPK.